Development of Comprehensive Framework Teaching Approaches and Methods for Group Counselling Laboratory Course in Higher Education Institution - Ghazali, Nor Mazlina; Awang Mat, Dayang Azra; Aden, Edris; Azhar Mazlan, Mohammad Nur; Mohd Roose, Aina Razlin; Fakhrul Nizam, Nur Hanis (Journal of Neonatal Surgery, 2025)
The study was conducted to develop a comprehensive framework of teaching methods and approaches for group counselling courses. It was carried out in two phases. The objectives of this study were: (i) to identify comprehensive teaching approaches and methods for group counselling courses, and (ii) to develop a structured framework for these teaching approaches and methods. This study utilized a mixed-method research design involving former and current students who had taken the Group Counselling Laboratory course. The results of the needs assessment analysis and group interviews with past students revealed that effective approaches include constructivism (a student-centred approach) and cognitivism (a teacher-centred approach). Additionally, the effective teaching methods identified for learning group counselling courses include interactive lectures, guided instruction, just-in-time teaching, experiential learning, case-based learning, role plays, and simulations, which are categorized as teacher-centred approaches. For the student-centred approach, the effective methods identified were fieldwork and clinical methods. The impact of these teaching approaches and methods was reflected in student performance, with 11 students obtaining an A, eight earning an A-, five receiving a B, and two earning a B-, out of a total of 26 students. Post-test feedback from the majority of students described the clarity of objectives, engagement, feedback on tasks, classroom management, assessment, differentiation of instruction, materials and learning plans, as well as the integration of technology presented in this course. In conclusion, the comprehensive framework of teaching approaches and methods for the Group Counselling course requires the integration of constructivism and cognitivism approaches, alongside teaching methods such as interactive lectures, guided instruction, just-in-time teaching, experiential learning, case-based learning, role plays, simulations, fieldwork, and clinical methods. Future researchers can explore other contexts, such as teaching delivery and course assessment.